2010
DOI: 10.1007/s10909-010-0166-7
|View full text |Cite
|
Sign up to set email alerts
|

Bose-Einstein Condensation in Multilayers

Abstract: The critical BEC temperature Tc of a non interacting boson gas in a layered structure like those of cuprate superconductors is shown to have a minimum Tc,m, at a characteristic separation between planes am. It is shown that for a < am, Tc increases monotonically back up to the ideal Bose gas T0 suggesting that a reduction in the separation between planes, as happens when one increases the pressure in a cuprate, leads to an increase in the critical temperature. For finite plane separation and penetrability the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Although at very low (or zero) temperatures and/or high densities the interaction between particles cannot be neglected, we focus on an interactionless boson gas to study the effects of a periodic confining potential on the properties of the system. We show that this simple model captures qualitatively the properties of real systems, including the emergence of thermal phase transitions and/or dimensional crossovers 38,39 . In the following section we describe our system model.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although at very low (or zero) temperatures and/or high densities the interaction between particles cannot be neglected, we focus on an interactionless boson gas to study the effects of a periodic confining potential on the properties of the system. We show that this simple model captures qualitatively the properties of real systems, including the emergence of thermal phase transitions and/or dimensional crossovers 38,39 . In the following section we describe our system model.…”
Section: Introductionmentioning
confidence: 84%
“…As the separation between planes is lowered, the critical temperature reaches a P 0 -dependent minimum value and then it is expected 38,39 to increase again towards T 0 . For systems with a x,y > λ 0 the numerical calculations for the critical temperature and specific heat are very sensitive to the number of energy bands considered.…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. [15] it was shown that a layered structure with plane separation a is revealed in the specific heat behavior as a function of temperature. For closely separated planes (a λ 0 ≡ h/ √ 2πmk B T 0 ), a minimum at T ≡ T min whose corresponding thermal wavelength scales with a as λ 2a is found in the C V vs T curves, where T 0 is the ideal gas BEC critical temperature.…”
Section: Introductionmentioning
confidence: 99%
“…(1) for has been extensively analized in Refs. 13,14 and 15 , where the allowed and forbidden energy-band structure is shown, and the importance of taking the full band spectrum has been demonstrated.…”
Section: Quantum Gases Whithin Multilayers and Multitubesmentioning
confidence: 99%